Examining continuance intention of online learning during COVID-19 pandemic: Incorporating the theory of planned behavior into the expectation–confirmation model - Li, Li; Wang, Qing; Li, Jinhui (Frontiers in Psychology, 2022)
COVID-19 pandemic has tremendously affected many industries in the world, including higher education. To cope with changes in the pandemic, online learning has become a prevalent means for university students to receive education. Based on the expectation-confirmation model (ECM) and the theory of planned behavior (TPB), this study aims to develop an integrated model, consisting of confirmation, perceived usefulness, satisfaction, perceived enjoyment, subjective norm, perceived behavioral control and continuance intention instruments, to predict Chinese university students’ continuance intention toward online learning. Using convenience sampling, we enrolled full-time university students who have used online learning platforms in November 2020. Data collected from 493 Chinese university students were analyzed by confirmatory factor analysis (CFA) and structural equation model (SEM) to test the model and hypotheses. All measurements of constructs used in this study are adapted by previous studies. The results show that perceived satisfaction, subjective norms, and perceived behavioral control were significantly associated with the continuance intention of online learning. Furthermore, the two components of the expectation–confirmation model (ECM), perceived usefulness and perceived enjoyment have a significant impact on the satisfaction of online learning. Notably, although confirmation of expectations had no direct impact on satisfaction, it was positively associated with perceived usefulness and perceived enjoyment. Implications and limitations were discussed.